The Relationship between Oil Palm Expansion and Income Inequality in Indonesia, Malaysia, the Philippines, and Thailand: International Trade Insights - Hasudungan, Albert; Raeskyesa, Dewa Gede Sidan (Journal of Entrepreneurship, Business and Economics, 2021)
This study aims to explore the relationship between the expansion of oil palm plantations and income inequality in Indonesia, Malaysia, Thailand, and the Philippines. The relationship was investigated using panel data analysis from 2000 to 2019. The results indicate a mixed effect of palm oil expansion on inequality, in which land use for oil palm farming has a significant and negative effect on income inequality as measured by the Gini Index. However, fertilizer consumption and yield in oil palm activities have positive relationships with income inequality. This suggests the importance of supporting equal access to both financing and capacity building. Lastly, this study presents scenarios with and without government intervention. Research paper Keywords: Palm Oil; Expansion; Inequality; International Trade; Data Panel Reference to this paper should be made as follows: Hasudungan. A., & Raeskyesa, D. G. S. (2021). The Relationship between Oil Palm Expansion and Income Inequality in Indonesia, Malaysia, the Philippines, and Thailand: International Trade Insights. Journal of Entrepreneurship, Business and Economics , 9 (2), 72–95.